2004
DOI: 10.1242/jcs.01544
|View full text |Cite
|
Sign up to set email alerts
|

Protein 4.1R regulates interphase microtubule organization at the centrosome

Abstract: In human red blood cells, protein 4.1 (4.1R) stabilizes the spectrin-actin network and anchors it to the plasma membrane. To contribute to the characterization of functional roles of 4.1R in nonerythroid cells, we analysed the effect of ectopic expression of 4.1R isoforms on interphase microtubules in fibroblastic cells. We found that specific 4.1R isoforms disturbed the microtubule architecture but not the actin cytoskeleton. Biochemical sedimentation and/or confocal microscopy analyses showed that the perice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…We tested our hypothesis by analyzing microtubule regrowth which was similar to that in controls. Interestingly, ectopic overexpression of a variant 4.1R isoform also does not impair microtubule nucleation/regrowth (52). We did find that 4.1R-depleted cells had a loss of focused microtubule arrays, thus confirming that 4.1R is involved in microtubule anchoring at centrosomes.…”
Section: Discussionsupporting
confidence: 58%
“…We tested our hypothesis by analyzing microtubule regrowth which was similar to that in controls. Interestingly, ectopic overexpression of a variant 4.1R isoform also does not impair microtubule nucleation/regrowth (52). We did find that 4.1R-depleted cells had a loss of focused microtubule arrays, thus confirming that 4.1R is involved in microtubule anchoring at centrosomes.…”
Section: Discussionsupporting
confidence: 58%
“…They participate in the dynamic interrelationships between the centrosome and the cytoarchitecture [24]. Spectrin and dynein is known to involve with early form of vesicles and aid in their transport to respective sites [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although the expression pattern of 4.1R in mature mammalian red cells is relatively simple, multiple isoforms of 4.1R with variable N-terminal extensions and internal sequences are expressed in nonerythroid cells, mainly as a result of extensive alternative splicing of the 4.1R-encoding pre-mRNA (Conboy, 1999;Tang et al, 1990). The localization of protein 4.1R in nonerythroid cells is not restricted to the subjacent area beneath the plasma membrane, as 4.1R has also been identified at the nucleoskeleton (De Carcer et al, 1995), the centrosome Perez-Ferreiro et al, 2004), the endoplasmic reticulum (Luque et al, 1999) and microtubules (Perez-Ferreiro et al, 2001), thereby showing that 4.1R functions at multiple sites in the cell. The interaction of protein 4.1R with zonula occludens (ZO)-2 (Mattagajasingh et al, 2000) and with -catenin and E-cadherin (Yang et al, 2009) suggested that 4.1R might act as a linker between tight and adherens junctions and the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%